Comparison of Dimensional Accuracy of (Pmma) Denture Base Material Relined with Molloplast B Soft Liner by Different Curing Methods. - Radhwan H Hasan; Shilan H Fatah (Erbil Dental Journal)
Background and objectives: The most common problem associated with the complete denture is the loss of retention after period of time therefore relining procedure is important in many cases, this study was done to compare the dimensional accuracy of PMMA before and after the application of Molloplast B Soft liner to the denture base material by different curing methods.